Mediações teórico-metodológicas no Serviço Social, estado e políticas sociais em Angola - Monteiro, Amor António (2020)
This paper examines the ontological, reflexive-analytical and technical-operational status of the measurement category, its relevance to theoretical–methodological and critical rigor in understanding the nature of Social Work in its connections and contradictions with the State and Social Policy in Angola. Analyzing the theoretical-methodological mediations present in the understanding and intervention of the Social Worker in the particular expressions of the social issue in Angola is the focus of this work. To this end, based on the Marxian theoretical framework and the authors linked to it, the ontological foundations of the modern state in Angola and its social function in the sociometabolic system of capital were analyzed. In this direction, making a historical rescue of the protoforms of social policies, we sought to capture their ontological foundations, analyzing the theoretical-methodological mediations that cross them, which are constitutive and give ethical-political direction to the profession and shape the profile of politics. in the country. Using bibliographical, documentary research and interpretation of various ideopolitical discourses, policies, programs and social projects that reveal ideas, proposals, purposes that different actors, Angolans and Portuguese presented and use to face the expressions of the “social question” in the period. colonial and nowadays, as well as the analysis of ninety-three Course Completion Papers advocated by Social Workers in 2017 and 2018 in Angola; It is concluded that there is no theory that has no reflection on social life and no social practices that do not use theoretical-methodological mediations. Rather, this is a constitutive, reflexive-analytical, and technical-operational category of the profession. The theoretical-methodological mediation expresses and is instituted in the movement and class struggles present in Angolan society in its different historical phases. In colonial times and after independence, the state in Angola, as a political representative of the capitalist class, used and used the ideological decay that is hegemonically expressed in positivism of a functionalist focus with moral characteristics, to interpret, intervene and give ideopolitical direction. their different tools to face the expressions of the social question